Three dimensional echocardiography in congenital heart defects - Shirali Girish (Wolters Kluwer Medknow Publications, 2008)
Three dimensional echocardiography (3DE) is a new, rapidly evolving modality for cardiac imaging. Important technological advances have heralded an era where practical 3DE scanning is becoming a mainstream modality. We review the modes of 3DE that can be used. The literature has been reviewed for articles that examine the applicability of 3DE to congenital heart defects to visualize anatomy in a spectrum of defects ranging from atrioventricular septal defects to mitral valve abnormalities and Ebstein′s anomaly. The use of 3DE color flow to obtain echocardiographic angiograms is illustrated. The state of the science in quantitating right and left ventricular volumetrics is reviewed. Examples of novel applications including 3DE transesophageal echocardiography and image-guided interventions are provided. We also list the limitations of the technique, and discuss potential future developments in the field.